Design and experimental analysis of morphing wing based on biomimicry - A, Mugeshwaran; Prasad Bacha, Guru; S, Rajkumar (International Journal of Engineering and Technology, 2018)
In this paper narrate about the study of aerodynamics in the multi-section morphing wing variation of baseline configuration to camber con-figuration. In particularly NACA 0012, section tried to morph as NACA 9312 camber section to achieve the lift to drag ratio in the flight condition based on the bio-mimicry. The CAD model and fabricated morphing wing in geometry scale of 20 cm chord and a 36 cm wing-span, with aluminum material ribs divided into 6 sections. Each section was able to rotate approximately 6 degrees without causing a discon-tinuity in the wing surface and also in order avoid the control surface based on the bio mimicry the morphing wing was designed and tested. DC-motor located at main spar with the two equal gear ratio the rib section used to morph the wing through the linear mechanical linkages. The aluminum ribs section are made through the EDM-Wire cut machining process for capable to actuate the morphing wing. In each sec-tion morphing wing can able provide up to 10 percent variation in the symmetrical airfoil to the cambered airfoil. The experimental test of the morphing was carried out in the cascade tunnel by force balancing method and the lift and drag output are compared.Â Â